Kikuchi Fujimoto lymphadenitis- an uncommon entity in the surgical outpatients: a case report - Panchal, Anuradha; Gautam, Raj; Mahadik, Abhishek; Chougle, Qurratulain; Shaffi, Mohammed Zeba (International Journal of Research in Medical Sciences, 2017)
Kikuchi Fujimoto lymphadenitis is a benign self-limiting disease with subacute necrotizing lymphadenopathy of unknown cause. The clinical, histopathological and immunohistochemical features point to viral etiology hence delaying diagnosis commonly. Clinicians and pathologists awareness of this disorder may prevent misdiagnosis and inappropriate treatment. We describe here a case of a young woman admitted under our care with fever and cervical lymphadenopathy. Cervical lymph node biopsy revealed the rare clinical disorder of Kikuchi Fujimoto lymphadenitis which is not thought of as a primary cause of lymphadenopathy in the Indian subcontinent where tuberculosis is widely prevalent.